ANALISIS FILOGENETIK GARCINIA SPP. BERDASARKAN SEKUENS GEN rRNA - Rara Erlina Oktafia; Badruzsaufari Badruzsaufari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Garcinia genus has a complicated taxonomy due to the high similarities in morphological characters of its members. The phylogenetic analysis on Garcinia species based on rRNA gene sequence intended to find out the evolutionary relationship amongst the species. This research employed 20 sequences of the rRNA gene of Garcinia species selected from the GenBank of the National Center for Biology Information (NCBI).  The sequences were aligned using ClustalW with the MEGA X application. A phylogenetic tree was constructed Maximum Likelihood method approximation and Kimura 2-parameter model. The results of the analysis showed that the cladogram had monophyletic parameter properties and classified into 3 clades. Clade I consisted of G. celebica, G. hombroniana, G. opaca, G. mangostana, G. malaccensis, G. penangiana, G. scortechinii, G. hanburyi, and G. urophylla. Clade II included G. atroviridis, G. bancana, G. forbesii, G. griffithii, G. cowa, G. nigrolineata, G. globulosa, and G. parvifolia. Clade III composed of G. rostrata, G. nervosa, and G. praininiana.  The species of Garcinia considered the most primitive and the closet to their ancestor is G. nervosa.